Acidentes de trânsito com motociclistas: um estudo social e participativo - Morais, Sandra Dalvi Quintaes de (2013)
INTRODUCTION: Thousands of young people are victims of traffic accidents worldwide. In Brazil, between 2006 to 2010, the period selected for this research analysis, the available databases recorded 94,160 deaths of young motorcyclists, aging between 15 and 24, which represented 40.8% of all deaths in the country for that period. In Uberlândia, at the Emergency Room of the Clinics Hospital of the Federal University of Uberlândia (HC-UFU), this reality is not different: between 2006 and 2010, there were 9,034 traffic accidents. Of these, 4,476 (49.5%) involved motorcyclists and 1,602 (35.8%) involved young people between 15 and 24 years of age. OBJECTIVE: To evaluate the causes and the perceptions of traffic accidents victims involving motorcycles in the city of Uberlândia, aged 18-24 years in 2010, and referred for treatment at the HC-UFU. METHODS: This is a retrospective study. Subjects were selected based on predetermined criteria: being male, aging between 18-24 years old at the time of the accident, having been involved in motorcycle accident in 2010 and having been referred to the service of the HC-UFU. We used a semistructured interview with both qualitative and quantitative questions, that was applied to fifteen male victims of traffic accidents with motorcycles in their homes or workplace. RESULTS: we found that 60% of victims still own a motorcycle, 20.4% use it as a means of transport to work, most acquired the motorcycle as a substitute to public transportation, 66.7% believed that there was no relationship between the number of motorcycles in transit and the number of accidents, 80% were driving the motorcycle at the time of the accident, 80% did not obey the traffic rules, 50% did not comply with the \"stop\" sign, 25% think it is essential to pay more attention in traffic to avoid accidents, the majority reported the need to change the driver s behavior, 33% consider the transit of Uberlândia as \"good\", 44% suggested an increase in transit supervision; 86.7% do not know any motorcyclists association, 48% suggested the need for more respect for traffic rules and more attention, 18% emphasized a reduction of driving speed; suggested campaigns using breath analyzer test, verification of driver s licenses, imprisonment and fines for violators. CONCLUSION: The study of accidents involving male motorcyclists aged between 15 and 24 years is relevant, because it provides an understanding of the main causes of these events, establishing measures to prevent and control the circumstances that predispose to such occurrences.